The Endurance of Love: Passionate and Companionate Love in Newlywed and Long-term Marriages - Mary Utne O’Brien; Jane Traupmann Pillemer; Elaine Hatfield; Yen-Chi L. Le (Interpersona: An International Journal on Personal Relationships, 2008)
Most theorists assume that the passage of time will have a very different impact on passionate versus companionate love. Passionate love is said to decline fairly quickly, while companionate love is thought to remain fairly stable (or actually increase) over time.This hypothesis was tested in two studies. In Study 1, we interviewed 53 newlywed couples soon after their marriages and again one year later, when presumably (for some) the “honeymoon was over.” In Study 2, we interviewed a random sample of 240 older women, ranging in age from 50-82, who had been married varying lengths of time. (The median length of marriage was 33 years.) We asked about their passionate and companionate love for their partners and their partner’s love for them. In Study 1, it was found that although newlywed men and women loved with equal passion, women tended to love their partners more companionately than they were loved in return. (This is in accord with previous research with dating couples.) The results for people married many years were more complex.Finally, we turned to the question with which we are most concerned: What impact does time have on love? In both Study 1 and Study 2, time did have a corrosive effect on love—but to our surprise it appeared to have an equally detrimental effect on both passionate and companionate love.